Basal ganglia infarct secondary to moya moya disease in a child with traumatic head injury: a case report and review of literature - Sagun Ghimire; Shikher Shrestha; Dinuj Shrestha; Kajan Ranabhat; Naresh Kharbuja; Sudarshan Awal (BMC Neurology)
Abstract Background Basal ganglia infarct following traumatic head injury is considered rare. Moreover moya moya disease resulting basal ganglia infarct in a child with traumatic head injury is much unusual. Though the line of management in such cases is straightforward along with good outcome following conservative management but early identification and diagnosis is mandatory to avoid grievous complications. Case presentation A 3 years old male with recent history of traumatic head injury following road traffic accident presented with weakness of left upper and lower limbs. On diagnostic evaluation there was right sided basal ganglia acute infarct. On further investigations basal ganglia infarct was secondary to moya moya disease. Patient was managed conservatively with single low dose anti platelets therapy, anti epileptic and was discharged with good functional outcome. Conclusion This case highlights that basal ganglia infarct can be secondary to moya moya disease in the background of traumatic head injury hence there is need for rigorous clinical correlation and timely diagnosis for the betterment of patients functional outcome.